Collective action and property rights for poverty reduction: Lessons from a global research project - Mwangi, Esther; Markelova, Helen; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2008)
To examine the role of the institutions of collective action and property rights on poverty reduction, the Systemwide Program on Collective Action and Property Rights (CAPRi) of the Consultative Group on International Agricultural Research (CGIAR) undertook a global research project with study sites in Ethiopia, Kenya, Uganda, Indonesia, India, Cambodia, and the Philippines. The main goal of the project was to contribute to poverty-reduction efforts by identifying effective policies and practices that enhance the ways that collective action and property rights are used to build secure assets and income streams for and by the poor. The project intended to provide policymakers, NGOs, and community groups with knowledge of the factors that strengthen the rights of the poor to land and water resources and lead to more effective collective action by the poor. Four CGIAR centers and two German universities conducted empirical research on the role of collective action and property rights for disadvantaged groups. The briefs in this set represent the case studies that were part of the project. The case studies rely on a variety of research methods, including qualitative and quantitative approaches, participatory action research, and experimental games. They also cover a variety of contexts within Africa and Asia, which will allow policymakers, researchers, and practitioners to further examine what constitutes poverty and affects the welfare of the poor between and within countries, and to draw comparisons.